Experimental and numerical studies on a new double-stage tandem nesting cyclone. (8th June 2021) - Yu, Guoyin; Dong, Sijie; Yang, Linna; Yan, Di; Dong, Kejun; Wei, Yi; Wang, Bo
Graphical abstract: Highlights: A new type of double-stage tandem nesting cyclone was designed. The removal efficiency of fine particles was significantly improved. The new double cyclone has great potential in the classification for three products. The numerical model for the double cyclone was established and verified. Abstract: This paper proposes a new type of gas cyclone separator, which nests an inner cyclone with a double-spiral inlet in an outer cyclone. Experiments were conducted to compare the separation performance of the new cyclone to that of the traditional Lapple cyclone. In addition, the flow fields and the particle collection in the two cyclones were simulated by the computational fluid dynamics (CFD) and compared. Compared with the traditional Lapple cyclone, the new double cyclone can present significantly improved collection efficiency, resulting from the two-stage separation and better symmetry of the flow field. On the other hand, the pressure drop of the new cyclone was only slightly elevated because of the low velocity in the outer cyclone. Moreover, this new double-stage cyclone separator can be further developed for particle classification, as the particles collected in the three outlets of the cyclone are in different size ranges.